Fermented oat vellie from high â-glucan oat bran - Gyran, Maiju; Mikola, Markku; Salovaara, Hannu (MTT, 2004)
Oats have great potential as an ingredient for non-dairy foods and are offering an alternative to soy-based ingredients. Like soy, oats can be used for yoghurt and milk type products. Oat-based ingredients also offer health benefits and technological functionality, and are easy to flavour. Fermented cereal snacks of yoghurt-type are called vellies. In this study the suitability of various high beta-glucan oat bran products for making oat vellie was tested. Eight commercially available probiotic starters and starter combinations composed of lactobacilli and bifidobacteria were used in fermentation experiments. The vellie was prepared from oat bran concentrate (Natureal) and water. The mixture was cooked and then cooled. After adding the starter the fermentation lasted 15 h at 37ºC. All oat bran products tested supported fermentation and the growth of bacteria resulting in a final pH of 3.7 to 4.2 depending on the starter. However, there were significant differences in the behaviour of the bacterial strains and starters in this substrate in terms of growth rate, acid production and other parameters. Certain commercially available starters are well suited to vellie fermentation. The colony forming units were 106 - 107 CFU/g and remained at that level during storage. The combination of a probiotic strain with high beta-glucan in a hydrated product suggests improved health benefits.
Keywords: Ka; oat; non-dairy; vellie; probiotic